SISTEM PENDUKUNG KEPUTUSAN REKOMENDASI PEMBERIAN BANTUAN SOSIAL DENGAN MULTI OBJECTIVE OPTIMIZATION BY RATIO ANALYSIS (MOORA) - Ramli, Zulhisham; Kambau, Ridwan Andi; Hariani, Hariani (Prodi Teknik Informatika Universitas Islam Negeri Makassar, 2024)
Cash Direct Assistance (BLT) is one of the conditional assistance programs from the government as a form of poverty alleviation program. The selection process of potential recipients of BLT in Lamatti Riaja Village, Sinjai Regency, it is not entirely accurate as it is still done manually, resulting in many recipients not meeting the criteria. Based on this, research is conducted to design a decision support system that will facilitate the automatic checking of data for eligible residents who are entitled to BLT funds for each disbursement. This aims to make the selection process more objective, time-efficient, and minimize potential errors in selecting BLT recipients. In this research, the Multi Objective Optimization By Ratio Analysis (MOORA) method is employed. The calculation process utilizes the MOORA algorithm, and the implementation of the system is in the form of a website using the System Development Life Cycle design method, providing good and accurate results. The testing method used is Black Box testing. This research produces a Decision Support System website with the implementation of a data management subsystem using MySQL. The simulation results of the BLT recipient data calculation using the MOORA algorithm minimize errors in the selection process for potential BLT recipients.